2020
DOI: 10.5194/cp-16-2055-2020
|View full text |Cite
|
Sign up to set email alerts
|

Early Jurassic climate and atmospheric CO<sub>2</sub> concentration in the Sichuan paleobasin, southwestern China

Abstract: Abstract. Climatic oscillations have been developed through the (Early) Jurassic from marine sedimentary archives but remain unclear from terrestrial records. This work presents investigation of climate-sensitive sediments and carbon and oxygen isotope analyses of lacustrine and pedogenic carbonates for the Early Jurassic Ziliujing Formation taken from the Basin in southwestern China. Sedimentary and stable isotope proxies manifest that an overall secular (semi)arid climate dominated the Sichuan Basin during t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…Our Δ47 SST for the Lower-Jurassic can be compared to published results from Earth System models that simulate past intervals of global warmth to discuss model-data discrepancies. Proxy-data indicate an atmospheric pCO2 of 1000±500 ppmv during the Early Jurassic, with maximum values of 1750±500 ppmv, i.e., 6x pre-295 industrial levels (PIL), during the T-OAE (McElwain et al, 2005;Li et al, 2020). Earth system models run at 6x PIL for Early Jurassic (Dera and Donnadieu, 2012) produce lower SST than those inferred from our Δ47 data, with a maximum model-data discrepancy of >15°C at high latitudes (Fig.…”
Section: Early Jurassic Latitudinal Temperature and δ 18 Ow Gradients 275mentioning
confidence: 64%
“…Our Δ47 SST for the Lower-Jurassic can be compared to published results from Earth System models that simulate past intervals of global warmth to discuss model-data discrepancies. Proxy-data indicate an atmospheric pCO2 of 1000±500 ppmv during the Early Jurassic, with maximum values of 1750±500 ppmv, i.e., 6x pre-295 industrial levels (PIL), during the T-OAE (McElwain et al, 2005;Li et al, 2020). Earth system models run at 6x PIL for Early Jurassic (Dera and Donnadieu, 2012) produce lower SST than those inferred from our Δ47 data, with a maximum model-data discrepancy of >15°C at high latitudes (Fig.…”
Section: Early Jurassic Latitudinal Temperature and δ 18 Ow Gradients 275mentioning
confidence: 64%
“…Based on high-resolution mineralogical and geochemical analyses, Zhou et al (2022) identified F I G U R E 8 Sedimentary characteristics of the upper sequence in facies association B. (a) Field photograph of outcrop showing the upper sequence in facies association B with highlighted box sections enlarged in (c-e); (b) sketch map of the upper sequence in facies association B, (c) Enlargement from (a) showing black coal seam in the upper sequence of facies association B, (d) Enlargement from (a) showing blocky rooted mudstone in the upper sequence of facies association B and (e) Enlargement from (a) showing plant fossils in the upper sequence of facies association B. three warm and humid climate intervals during the PliensbachianStage in the study area, which are generally correlated to the increasing atmospheric CO 2 concentrations(Li et al, 2020; Figure12). Therefore, we mainly evaluate the influences of climate change on depositional evolution here and suggest the depositional model during the Pliensbachian Stage in the northern Qaidam Basin (Figure12).In Episode I, the basin is in the initial stage of receiving sedimentation.…”
mentioning
confidence: 76%
“…However, the climate in the Qaidam Basin is characterized by multiple significant perturbations (Hu et al, 2020; Zhou et al, 2022). Based on high‐resolution mineralogical and geochemical analyses, Zhou et al (2022) identified three warm and humid climate intervals during the Pliensbachian Stage in the study area, which are generally correlated to the increasing atmospheric CO 2 concentrations (Li et al, 2020; Figure 12). Therefore, we mainly evaluate the influences of climate change on depositional evolution here and suggest the depositional model during the Pliensbachian Stage in the northern Qaidam Basin (Figure 12).…”
Section: Depositional Evolution In the Pliensbachian Stagementioning
confidence: 99%
“…Proxy data indicate an atmospheric pCO 2 of 1000 ± 500 ppmv during the Early Jurassic, with maximum values of 1750 ± 500 ppmv, i.e. 6× pre-industrial levels (PILs), during the T-OAE (McElwain et al, 2005;Li et al, 2020). Earth system models run at 6× PIL for the Early Jurassic (Dera and Donnadieu, 2012) or Cretaceous-Eocene paleogeography almost invariably produce lower SSTs than those inferred from our 47 data, with a maximum modeldata discrepancy of > 15 • C at high latitudes (Fig.…”
Section: Early Jurassic Latitudinal Temperature and δ 18 O W Gradientsmentioning
confidence: 99%